Maturation of peroxisomes in differentiating human hepatoblastoma cells (HepG2): possible involvement of the peroxisome proliferator-activated receptor α (PPARα) - Stier, Harald; Fahimi, H. Dariush; Völkl, Alfred; Baumgart-Vogt, Eveline; Van Veldhoven, Paul P.; Mannaerts, Guy P. (Differentiation, 1998)
We have studied the alterations of peroxisomes in the human hepatoblastoma cell line HepG2, induced to differentiate by long-term cultivation (20 days without passaging) using morphological and biochemical techniques as well as mRNA analysis. Ultrastructural studies revealed alterations in shape and size of peroxisomes, with significant increases in mean diameter and formation of small clusters exhibiting heterogeneous staining for catalase after 20 days in culture. These alterations of peroxisomes correspond to the changes described during the maturation process from prenatal to adult human hepatocytes. As revealed by Northern and Western blotting there was marked elevation of the mRNA (190%) and protein (180%) of the peroxisomal branched-chain acyl-CoA oxidase. This protein is the key regulatory enzyme for the side chain oxidation of cholesterol for bile acid synthesis, a pathway associated with mature hepatocytes. Concomitantly a marked increase of bile canaliculi was noted by light and electron microscopy. This differentiation process was confirmed also by the increase of albumin synthesis (mRNA: 160%; protein: 190%) which is generally used as a differentiation marker of hepatocytes in culture. Interestingly, the mRNA for peroxisome proliferator-activated receptor α (PPARα) increased drastically by almost 390% and its correponding protein by 150%, suggesting its involvement in maturation of the peroxisomal compartment in differentiating HepG2 cells. In contrast to the well-known increases during the drug-induced peroxisome proliferation of cytochrome P450 4A, multifunctional enzyme 1, palmitoyl-CoA oxidase and the 70-kDa peroxisomal membrane protein, those proteins were either not altered or only slightly elevated during the differentiation process, suggesting that peroxisome proliferation and maturation are two distinct and differentially regulated processes.
Elektronische Reproduktion der Druck-Ausgabe 30. November 2009
Gesehen am 15.01.2025